PENDIDIKAN KARAKTER KRISTEN SEBAGAI UPAYA MENGEMBANGKAN SIKAP BATIN PESERTA DIDIK - Anton Nainggolan (Sekolah Tinggi Teologi Excelsius, 2020)
AbstractSuccessful education is education that can shape human behavior, not just equip people with knowledge and information. Research Objectives: (1). What is the meaning of Christian character education? (2). What is the role of Christian character education in the development of the inner attitudes of students? (3). What Are the Natural Implications of Human Total Disability? Methods: This research was conducted using a qualitative method with a literature study approach. Research Results: (1). Education that shapes and develops the inner attitude of students so that they are able to behave and behave wisely, and be responsible in their daily lives as Christians (2). Character education plays an important role in the personal formation of students. In the process various noble morals are discussed, including honesty, virtue, courage, discipline, generosity, tolerance, and responsibility. (3). Proper character education must actually begin with a personal encounter with Jesus. Character education and learning are tools, media or means in the formation of the human person. AbstrakPendidikan yang berhasil adalah pendidikan yang dapat membentuk perilaku manusia, bukan sekedar membekali manusia dengan pengetahuan dan informasi saja. Tujuan Penelitian: (1). Apakah pengertian pendidikan karakter Kristen? (2). Bagaimanakah peran pendidikan karakter kristen terhadap pengembangan sikap batin peserta didik? (3). Bagaimanakah Implikasi Natur Ketidakmampuan Total Manusia? Metode: Penelitian ini dilakukan dengan metode Kualitatif dengan pendekatan studi pustaka. Hasil Penelitian: (1). Pendidikan yang membentuk dan mengembangkan sikap batin peserta didik supaya mampu bersikap dan berperilaku bijak, serta bertanggung jawab dalam kehidupannya sehari-hari sebagai orang Kristen (2). Pendidikan karakter berperan penting dalam pembentukan pribadi peserta didik. Dalam proses itu berbagai akhlak luhur diperbincangkan, termasuk kejujuran, kebajikan, keberanian, kedisiplinan, kemurahan, toleransi, tanggung jawab. (3). Pendidikan karakter yang tepat sebenarnya harus dimulai dengan perjumpaan pribadi dengan Yesus. Pendidikan dan pembelajaran karakter merupakan alat bantu, media atau sarana dalam pembentukan pribadi manusia.